Glioblastoma stem cells and the importance of endolysosomes to keep them in the niches - Rogister, Bernard (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
It’s not necessary to stress out the bad outcome of patients with glioblastoma (GBM): after the classical Stupp’s protocol (large surgical resection, radiotherapy and chemotherapy using temozolomide), the general survival rate is globally 9% 2 years after diagnosis (1). This situation is mainly the consequence of a systematic tumor recurrence. Although not yet fully experimentally demonstrated, it is more and more accepted that these recurrences could be due to a subpopulation of GBM cells, the glioblastoma stem cells (GSCs) (2). At least, those GSCs have been demonstrated to play a role in GBM initiation and therapeutic resistance. Indeed, they are regarded as “stem cells” because they express stem cells markers, can differentiate into various cell types and are able to self-renew. Self-renewal is more restrictive than cell proliferation as it implies that at least one daughter cell is roughly identical to the mother cell, including the ability to perform the same number of cell cycles (3).